Towards contextualized complex systems approaches to scaling-up hepatitis B birth-dose vaccination in the African region: a qualitative systematic review - Tasneem Solomon-Rakiep; Tasneem Solomon-Rakiep; Jill Olivier; Edina Amponsah-Dacosta (Frontiers in Public Health, 2024)
BackgroundDespite the longstanding implementation of universal hepatitis B infant vaccination programs, the World Health Organization African region (WHO AFRO) maintains the highest prevalence (2.5%) of chronic hepatitis B virus (HBV) infection among children ≤5 years of age. Scaling-up hepatitis B birth-dose (HepB BD) vaccination could avert mother-to-child transmission of HBV infection and advance regional progress towards eliminating viral hepatitis.ObjectiveTo describe whether – and how – complexities within the health system or intervention influence the performance of HepB BD vaccination programs in the WHO AFRO.MethodsUsing a complexity perspective, we conducted a qualitative systematic review of literature published between 2009–2022. A Boolean search strategy retrieved relevant literature indexed in PubMed, EBSCOhost databases, Scopus, and Web of Science, with supplementary searches conducted to identify any missed articles. No language restrictions were applied. Data extraction, synthesis and analysis were guided by a systems-based logic model tailored to systematic reviews of complex interventions.ResultsOur search yielded 672 published records. Of these, 28 (26 English, 2 French) were eligible for inclusion. Among the 12 WHO AFRO member states represented, the origin of evidence weighted highest in Nigeria (n = 12) and Senegal (n = 5). The performance of HepB BD vaccination programs across member states are influenced by underlying complexities across eight cross-cutting themes: (i) availability and interpretation of HepB BD vaccination policies, (ii) capacity of vaccine supply and cold chain systems, (iii) availability of equitable and sustainable financing, (iv) capacity and capability of health care workers (HCWs), (v) immunization monitoring systems and impaired feedback loops, (vi) influence of context vs system design on the timeliness of vaccination, (vii) maternal knowledge and socio-economic factors, and (viii) wider contextual factors (geography, climate, cultural practices).ConclusionCountries looking to introduce, or scale-up HepB BD vaccination programs will benefit from careful consideration of components of the intervention design that are dependent on the end-user’s context and capabilities in accessing the vaccine; the adherence and interpretation of essential components of the policy; the provision of adequate support of stakeholders specifically HCWs and government ministries; and the need for innovative approaches to underlying complexities. Lessons offered by these African experiences provide pragmatic approaches to successfully implementing HepB BD vaccination programs in the region.